Lexicon of Global Melodrama - Paul, Heike; Marak, Sarah; Gerund, Katharina; Henderson, Marius (Global Sentimentality, 2022)
This new go-to reference book for global melodrama assembles contributions by experts from a wide range of disciplines, including cultural studies, film and media studies, gender and queer studies, political science, and postcolonial studies. The melodramas covered in this volume range from early 20th century silent movies to contemporary films, from independent ›arthouse‹ productions to Hollywood blockbusters. The comprehensive overview of global melodramatic film in the Lexicon constitutes a valuable resource for scholars and practitioners of film, teachers, film critics, and anyone who is interested in the past and present of melodramatic film on a global scale. The Lexicon of Global Melodrama includes essays on All That Heaven Allows, Bombay, Casablanca, Die Büchse der Pandora, In the Mood for Love, Nosotros los Pobres, Terra Sonâmbula, and Tokyo Story.